Kinetika Release Mikrokapsul Oleoresin Jahe Merah - Jayanudin Jayanudin; R Rochmadi; Meri Yulvianti; Ahmad Imanudin; Tri Rina Sari (Reaktor, 2016)
Abstract RELEASE KINETICS OF RED GINGER OLEORESIN MICROCAPSULES. Red ginger oleoresin microcapsule is used to protect the active component of medicine against the negative effect of the environment, thus the microcapsule can be applied in the pharmaceutical industries. Kinetic release is used to determine the rate of red ginger oleoresin microcapsule release in human body system. The models used for this purpose are zero order, first order, Higuchi, and Korsmeyer-Peppas. These models were completed by using graphical method to get the determination coefficient (R2). The aims of this research are to determine the effect of Tripolyphosphate (TPP) concentration towards microcapsule release, to determine the red ginger oleoresin microcapsule kinetic release, and to characterize the morphology and particle sizes of red ginger oleoresin microcapsule using the Scanning Electron Microscopy (SEM). The encapsulation method was started by emulsifying process of chitosan-alginate, with various ratios of Chitosan-Alginate such as 1:2, 1:1, 2:1, and 20 gram red ginger oleoresin, and also the addition of TPP, with various concentrations for as much as 3%, 4 %, and 5%, as the crosslinking agent. The emulsion was forwarded to the spray dryer machine to produce the red ginger oleoresin microcapsule. Then, the microcapsule was treated with the mixture of KH2PO4 and NaOH (pH 6.8) for 1 hour, and sample was taken for every 10 minutes for the dissolution test. The result showed that the increase of TPP concentration will reduce the release velocity of the active compound. Kinetic model with the highest value of R2 was the Korsmeyer-Peppas model. Keywords: alginate; encapsulation; release kinetics; chitosan red ginger oleoresin;   Abstrak Mikrokapsul digunakan untuk melindungi oleoresin jahe merah yang sensitif terhadap pengaruh lingkungan, sehingga dapat diaplikasikan dalam bidang farmasi. Kinetika release digunakan untuk menentukan kecepatan release mikrokapsul oleoresin jahe merah, model yang digunakan adalah model order nol, order satu, model Higuchi, dan Model Korsmeyer-Peppas. Penyelesaian model-model ini menggunakan metode grafis dengan menentukan koefisien determinasi (R2). Tujuan penelitian ini adalah menentukan pengaruh konsentrasi sodium tripolifosfat (TPP) dan rasio berat antara kitosan dan alginate sebagai penyalut terhadap kinetika release dan karakterisasi morfologi mikrokapsul oleoresin jahe merah.  Metode enkapsulasi dimulai dengan pembentukan emulsi dari penyalut kitosan-alginat dengan rasio 1:2; 1:1; 2:1 dan 20 gram oleoresin jahe merah, penambahan TPP 3%, 4% dan 5% untuk cross-link. Emulsi dialirkan ke spray dryer untuk menghasilkan mikrokapsul oleoresin jahe merah. Uji disolusi menggunakan medium basa dengan mencampurkan KH2PO4 dan NaOH (pH 6,8) sampel diambil tiap 10 menit selama 1 jam. Hasil penelitian yang telah dilakukan didapat peningkatan konsentrasi TPP akan menurunkan kecepatan releasenya, model model kinetika dengan nilai R2 terbesar adalah model Korsmeyer-Peppas. Kata kunci: alginat; enkapsulasi; kinetika release; kitosan; oleoresin jahe merah